TOLAKI CUSTOMARY LEGAL TRADITION IN SAMBEANI VILLAGE: A STUDY OF ITS IMPLEMENTATION AND IMPLICATIONS TOWARDS SOCIETY - Syaiful Arpin; Sabri Guntur (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Custom is an unwritten legal system implemented by indigenous communities, such as the Tolaki community in Sambeani Village, Southeast Sulawesi. Tolaki customary law protects social and cultural values in addition to resolving disputes. However, during the era of modernization and the increasingly strong dominance of national law, the existence and implementation of customary law began to experience difficulties. This study is crucial for understanding how Tolaki customary law is still applied and how it impacts the community's social life. This research aims to explain how Tolaki customary law is implemented in Sambeani Village, analyze its function and role in conflict resolution, and evaluate its impact on the social structure and customs of the local community. The method used is descriptive qualitative with a legal ethnography approach. Data collection was carried out through participatory observation, in-depth interviews with traditional leaders, village officials and community members as well as documents related to Tolaki customary law. Local policy recommendations for preserving and strengthening the role of customary law in resolving conflicts at the village level and (3) Digital documentation in the form of narratives and visualizations of Tolaki customary law practices as a form of preserving local culture. The results of this study on the Tolaki customary law tradition in Sambeani Village, Abuki District, Konawe Regency show that customary law still plays an important role in regulating the social life of the local community. Customary law is not only considered as a rule that is held traditionally, but is also considered as a value system that binds, shapes behavior, and maintains harmonious social relations between citizens. The implementation of customary law based on deliberation, mutual cooperation, and respect for traditional figures shows that collective values are still highly valued by the community.